Vitamin K protects against lipopolysaccharide-induced intestinal inflammation in piglets by inhibiting the MAPK and PI3K-AKT pathways - Wang, Huakai; Ma, Ruiyu; Qi, Renrong; Liu, Zhen; Li, Yinghao; Wu, Xudong; Zhao, Chunfang; Ma, Qiugang; Zhan, Kai (Frontiers in Nutrition, 2025)
BackgroundThe benefits of Vitamin K (VK) in mitigating inflammation have been well-established, while the underlying mechanisms remain not yet fully elucidated. This study aimed to investigate its protective effects and underlying mechanisms in LPS-induced intestinal inflammation of piglets.MethodsIn a 21-day study, 24 weaned piglets were randomly assigned to 4 groups: CON group (basal diet), VK group (basal diet + 4.5 mg/kg VK3), LPS group (basal diet + LPS challenge), LPS+VK (basal diet + 4.5 mg/kg VK3 + LPS challenge). On day 21, LPS or saline was administered to the piglets by intraperitoneal injection. The IPEC-J2 cells were treated with or without VK and LPS for 24 h and analyzed with various assays.ResultsMorphological analysis revealed that VK significantly restored the decreased villus height and ratio of villus height to crypt depth induced by LPS. VK effectively upregulated tight junction proteins claudin-1 expression. Furthermore, VK notably suppressed the overexpression of TNF-α, IL-1β, IL-6, and IL-8, as well as the concentrations of diamine oxidase (DAO) and reactive oxygen (ROS), while restoring the reduced expression of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD). The combined analysis of transcriptome and proteome, as well as the Western blot verification, indicated that VK mainly mediates the restriction of the MAPK and PI3K-AKT signaling pathways. Moreover, VK relieved gut microbiota dysbiosis, such as decreasing in Spirochaetato.ConclusionThese results indicated that VK alleviated intestinal inflammation in piglets by inhibiting the MAPK and PI3K-AKT signaling pathways as well as the regulation of in the gut microbiota.